Toksisitas Insektisida Organofosfat Dan Karbamat Terhadap Jentik Nyamuk Culex quinquefasciatus - Endang Puji Astuti (ASPIRATOR - Journal of Vector-borne Disease Studies, 2009)
Abstract. Culex quinquefasciatus mosquito is increasing problem of public health, being the vector responsible for West Nile Virus and Filariasis. Clorpirifos (Organofosfat) and Metonil (Carbamat) were known to posses insecticide activity against insect. The study was aimed to examine effectiveness of Klorpirifos and Metonil as larvicide against C. quinque-fasciatus larval. Klorpirifos a significantly higher larvicidal activity against 3th-4th instar larvae of C. quinquefasciatus than Metonil. The larval mortality was observed after 24 h ex-posure. The LC95 value of Klorpirifos and Metonil were 3,139 mg/lt and 9,045 mg/lt, against C. quinquefasciatus. The mixed of both insecticide was LC95 value 2,823 mg/lt. The result of this study suggested that Klorpirifos more effective larvicide against C. quinquefasciatus than Metonil.